Monster loyalty : how Lady Gaga turns followers into fanatics - Huba, Jackie (Portfolio/Penguin, 2013)
"Marketing expert Jackie Huba explores Gaga's biography and fan philosophy and isolates the seven lessons any business can learn from her ... And while not all businesses want to stand out the way she does, any business can win big by creating monster loyalty"--Amazon.com